The Application of Deep Breathing Relaxation Therapy to Control Blood Pressure in Hypertensive Patients in RT 01 RW 05 Kedung Kresik Utara, Argasunya Harjamukti Village, Cirebon City - Afif Alwan Izuddin, Mohamad; Erna Marisa, Dewi; Karlina, Nonok (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hypertension is one of the chronic diseases whose prevalence continues to increase globally. In addition to pharmacological therapy, non-pharmacological interventions such as deep breathing relaxation have been shown to contribute to lowering blood pressure through their effects on the autonomic nervous system and stress response. Method: This study employed a descriptive method with a case study approach on one patient meeting the criteria for hypertension, who underwent deep breathing relaxation 15 times, divided into 3 cycles. In each cycle, the patient was instructed to take 5 deep breaths with one rest period. Result: The results of this study showed that after three days of deep breathing relaxation intervention, the patient reported feeling more relaxed, and blood pressure improved from 158/118 mmHg to 126/108 mmHg. Conclusion: Deep breathing relaxation can be an effective management strategy for controlling blood pressure in conjunction with medication.